Transfer Of Land Rights Between Husband And Wife To Petak Palaku (Maskawin) According To Customary Law Of The Dayak Ngaju Tribe In Central Kalimantan - G. Satu, Yosep Pangarinah (International Significance of Notary, 2024)
Abstract : My pal plot is the land of demand (maskawin). Dayak people always put women in the main position. This can be seen from the daily life of society that always prioritizes women. My pal is the absolute right of the wife. The husband has no right to sell or mortgage it to another party. However, in certain circumstances, women who are given dowries in the form of plots want to make transfers in their own names to secure their rights, constrained by rules that do not allow any transfer between husband and wife. This study analyzes the basis of the transition and the process of transferring land rights between husband and wife according to the customary law of the Ngaju Dayak Tribe in Central Kalimantan. This research uses empirical juridical methods with sociological, anthropological, and conceptual approaches. With the result that the basis for the transfer of land rights between husband and wife is a Land Certificate (SKT) or Land Statement Letter (SPT) issued by Kelurahan/Village, as the basis for applying for the issuance of certificates for land that has not been certified. As for land that has been certified, the basis for the transfer of rights between husband and wife is a Marriage Certificate or marriage book. While the process of transferring land rights between husband and wife is the same as other rights transfer processes, the difference is the basis of rights that must attach SPT, SKT and Marriage Book or Marriage Certificate.Keywords: Petak Palaku, Transfer of Land Rights Between Husband and Wife, Dayak Ngaju